Standardization of pulmonary ventilation technique using volume-controlled ventilators in rats with congenital diaphragmatic hernia - Rodrigo Melo Gallindo; Frances Lilian Lanhellas Gonçalves; Rebeca Lopes Figueira; Ana Leda Bertoncini Simões; Lourenço Sbragia (Revista do Colégio Brasileiro de Cirurgiões)
OBJECTIVE: To standardize a technique for ventilating rat fetuses with Congenital Diaphragmatic Hernia (CDH) using a volume-controlled ventilator. METHODS: Pregnant rats were divided into the following groups: a) control (C); b) exposed to nitrofen with CDH (CDH); and c) exposed to nitrofen without CDH (N-). Fetuses of the three groups were randomly divided into the subgroups ventilated (V) and non-ventilated (N-V). Fetuses were collected on day 21.5 of gestation, weighed and ventilated for 30 minutes using a volume-controlled ventilator. Then the lungs were collected for histological study. We evaluated: body weight (BW), total lung weight (TLW), left lung weight (LLW), ratios TLW / BW and LLW / BW, morphological histology of the airways and causes of failures of ventilation. RESULTS: BW, TLW, LLW, TLW / BW and LLW / BW were higher in C compared with N- (p <0.05) and CDH (p <0.05), but no differences were found between the subgroups V and N-V (p> 0.05). The morphology of the pulmonary airways showed hypoplasia in groups N- and CDH, with no difference between V and N-V (p <0.05). The C and N- groups could be successfully ventilated using a tidal volume of 75 ìl, but the failure of ventilation in the CDH group decreased only when ventilated with 50 ìl. CONCLUSION: Volume ventilation is possible in rats with CDH for a short period and does not alter fetal or lung morphology.